2022
DOI: 10.1111/jcpe.13639
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of stage IV periodontitis: The EFP S3 level clinical practice guideline

Abstract: Background: The recently published clinical practice guideline (CPG) for the treatment of periodontitis in stages I-III provided evidence-based recommendations for the treatment of periodontitis patients, defined according to the 2018 classification. Stage IV periodontitis shares the severity and complexity characteristics of stage III periodontitis, but includes the anatomical and functional sequelae of tooth and periodontal attachment loss (tooth flaring and drifting, bite collapse, etc.), which require addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
165
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(169 citation statements)
references
References 156 publications
2
165
0
2
Order By: Relevance
“…Precision in the definition of staging can translate into in the possibility of framing and planning the treatment of periodontal patients in accordance with the guidelines issued by the European Federation of Periodontology (Herrera et al, 2022;Sanz, Herrera, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precision in the definition of staging can translate into in the possibility of framing and planning the treatment of periodontal patients in accordance with the guidelines issued by the European Federation of Periodontology (Herrera et al, 2022;Sanz, Herrera, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…
A periodontitis case should be defined using the staging and grading system proposed in the 2018 Classification of Periodontal and Peri-Implant Diseases and Conditions (Caton et al, 2018;Tonetti et al, 2018). Accurate and consistent case definitions are critically important, as they can have an impact in estimating the prevalence of periodontitis (Stødle et al, 2021), in assessing the actual need for periodontal therapy (Herrera et al, 2022;Sanz, Herrera, et al, 2020), in the definition of the periodontal prognosis (Saleh et al, 2022;Takedachi et al, 2022) and may influence the results and associations presented in the studies (Deng et al, 2021;Goergen et al, 2021).The consistency and accuracy among periodontal experts, general dentists and undergraduate dental students in defining periodontitis cases using the staging and grading system were first evaluated by Marini et al (2021). It was showed that intra-rater agreement was almost perfect, whilst inter-rater agreement was moderate.
…”
mentioning
confidence: 99%
“…A fumaça do cigarro convencional prejudica quase todos os órgãos do corpo e é a principal causa de morte nos Estados Unidos e no mundo. Havendo um surto levando a óbitos em 2019 devido a lesões pulmonares associado ao seu uso 11 A doença periodontal é classicamente caracterizada pela alteração no periodonto podendo levar a destruição progressiva dos tecidos moles e duros do complexo periodontal, mediada por uma interação entre comunidades microbianas disbióticas e respostas imunes aberrantes nos tecidos gengivais e periodontais 3,12 O tabagismo tem sido reconhecido como um importante fator de risco para a doença periodontal, afetando a prevalência, gravidade, progressão e resposta ao tratamento da doença, perdendo apenas para o biofilme 9 . Apesar de necessitar de mais estudos e levando em consideração as alterações do microbioma subgengival em fumantes diagnosticados com periodontite e sem periodontite, tornando-os provavelmente mais propensos a doenças periodontais e o agravamento da doença periodontal 13 .…”
Section: Revisão De Literaturaunclassified
“…The host reaction to the bacterial plaque triggers the production of inflammatory mediators, which can contribute to periodontal damage when exceeding a threshold [ 3 ]. Periodontitis signs include clinical attachment loss, gingival recession, and alveolar bone loss [ 4 ]. It is a serious public health problem because it causes considerable morbidity and is the main cause of adult tooth loss, but early detection of its symptoms (such as gingival redness, swelling and bleeding, or bad breath and painful mastication) could prevent its expansion and development of significant clinical consequences, through adequate treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis signs include clinical attachment loss, gingival recession, and alveolar bone loss [ 4 ]. It is a serious public health problem because it causes considerable morbidity and is the main cause of adult tooth loss, but early detection of its symptoms (such as gingival redness, swelling and bleeding, or bad breath and painful mastication) could prevent its expansion and development of significant clinical consequences, through adequate treatment [ 4 ]. Periodontitis therapy involves mechanical plaque reduction, removal of local irritants, and the use of antibacterial medicines [ 4 ].…”
Section: Introductionmentioning
confidence: 99%